Myosin V Regulates Spatial Localization of Different Forms of Neurotransmitter Release in Central Synapses - Maschi, Dario; Gramlich, Michael W.; Klyachko, Vitaly A. (Frontiers in Synaptic Neuroscience, 2021)
Synaptic active zone (AZ) contains multiple specialized release sites for vesicle fusion. The utilization of release sites is regulated to determine spatiotemporal organization of the two main forms of synchronous release, uni-vesicular (UVR) and multi-vesicular (MVR). We previously found that the vesicle-associated molecular motor myosin V regulates temporal utilization of release sites by controlling vesicle anchoring at release sites in an activity-dependent manner. Here we show that acute inhibition of myosin V shifts preferential location of vesicle docking away from AZ center toward periphery, and results in a corresponding spatial shift in utilization of release sites during UVR. Similarly, inhibition of myosin V also reduces preferential utilization of central release sites during MVR, leading to more spatially distributed and temporally uniform MVR that occurs farther away from the AZ center. Using a modeling approach, we provide a conceptual framework that unites spatial and temporal functions of myosin V in vesicle release by controlling the gradient of release site release probability across the AZ, which in turn determines the spatiotemporal organization of both UVR and MVR. Thus myosin V regulates both temporal and spatial utilization of release sites during two main forms of synchronous release.